The influence of aluminium on the overall properties of SnO2-based varistors - Parra, Rodrigo; Maniette, Yves; Varela, José Arana [UNESP]; Castro, Miriam S. (Springer, 2007)
The influence of aluminium on the development of the microstructure and on the electrical behaviour of the SnO2 center dot Co3O4 center dot Nb2O5 typical varistor system was studied. Two sources of Al were used, alumina (Al2O3) and boehmite (AlO(OH)). The microstructural features were characterised with scanning (SEM) and transmission (TEM) electron microscopies. The different phases present in the studied samples were also studied with XRD, EDS and electron diffraction patterns of selected areas (SAED). Particles containing Sri, Co, Al, and O were unveiled with TEM. Impedance spectroscopy measurements and current density versus electric field characteristics revealed superior electrical properties for samples with AlO(OH). The higher non-linearity (alpha = 19) was achieved with the addition of 0.1% mol of boehmite. The influence of the secondary phases on the electrical properties is also addressed in this work.